Closing formulae and transmission of cultural values in Samuel Richardson's "Letters Written to and for Particular Friends" (1741) - Shvanyukova, Polina (Status Quaestionis, 2018)
Pragmatic functions and the meaning-making potential of formulaic epistolary elements such as salutations, address forms, opening and closing formulae in historical correspondence have attracted considerable scholarly attention in recent years. In the wake of these studies, the present paper will extract and examine the inventory of eighteenth-century closing formulae in Samuel Richardson’s Letters Written to and for Particular Friends (1741). The aim of the investigation will be to show how these formulaic elements can assume multiple pragmatic functions, among which the transmission of cultural values and norms of conduct becomes especially prominent. Keywords: epistolary discourse, closing formulae, Historical Pragmatics, Samuel Richardson, transmission of values and norms